The Influence of Personal Hygiene Education in Elderly At Banjar Pemalukan Desa Peguyangan - Desi Nopitasari; AA Istri Putra Kusumawati; Ika Setya Purwanti (Stikes Wira Medika Bali, 2017)
Personal Hygiene is very important for prevention diseases, Personal Hygiene in Elderly, including hair, mouth and teeth, and genetalia. To get a good and right Personal Hygiene, needs good knowledge. The purpose of this research is to know The Influence of Education to Personal Hygiene elderly at Banjar Pemalukan Desa Peguyangan in 2017. Method :This research use One Group Pre-Post test Design. Total sample is about 43 elderly at Banjar Pemalukan Desa Peguyangan . Result : The result of the research shows that before researcher give the Personal Hygiene Education, gets 7 elderly that less knowledge about the Personal Hygiene, and 36 elderly that has enough knowledge about the Personal Hygiene. After researcher give the Personal Hygiene Education, gets 7 elderly that still enough knowledge about the Personal Hygiene and 27 elderly that has better knowledge about the Personal Hygiene. The result of the behavior after researcher give the education, 16 elderly shows good behavior personal hygiene. Discussion : Based on Wilcoxon Signed Rank Test gets p-value=0.000 means that there are an influence of Personal Hygiene Education in elderly At Banjar Pemalukan Desa Peguyangan .